Native Martiniquan, Trinidad B.W.I. - (:unkn) unknown (Maillard's, Trinidad [Printed in Germany], 2008)
Photo of a French Creole woman in native wear.
Colour: Blue, orange, pink and purple hues; Style: Portrait; Other: Unbordered, Divided
Keywords: Postcards; Women--Trinidad and Tobago; Ethnic costume--Martinique; Creoles--Martinique; Headgear--Martinique; Jewelry--Martinique; Bracelets--Martinique; Earrings--Martinique; Necklaces--Martinique; Clothing and dress--Trinidad and Tobago; Women, Creole (Martinique)